2021
DOI: 10.1093/annweh/wxab055
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and Comparing Emissions of Dust, Respirable Crystalline Silica, and Volatile Organic Compounds from Natural and Artificial Stones

Abstract: The frequency of cases of accelerated silicosis associated with exposure to dust from processing artificial stones is rapidly increasing globally. Artificial stones are increasingly popular materials, commonly used to fabricate kitchen and bathroom worktops. Artificial stones can contain very high levels of crystalline silica, hence cutting and polishing them without adequate exposure controls represents a significant health risk. The aim of this research was to determine any differences in the emission profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 10 publications
3
26
0
Order By: Relevance
“…This organic content can represent up to 14.3 wt.% of ES [ 32 ].These compounds are part of the resins used in manufacturing and reach the lungs as part of the dust particles inhaled during the working processes (cutting, drilling, polishing, etc.). Recently, Halls and colleagues have detected measurable concentrations of a wide range of VOCs emitted when cutting ES [ 42 ]. Although we do not know the pathogenic role of these compounds in ES workers, it should be taken into account that subchronic exposure to low-dose VOCs (formaldehyde, benzene, toluene, and xylene) produces bronchial and lung inflammation in animal models [ 43 ] and some low molecular weight PAHs, such as phenanthrene and fluorene, induce oxidative stress and inflammation in human lung epithelial cells and the combined action of both is more potent than individually [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This organic content can represent up to 14.3 wt.% of ES [ 32 ].These compounds are part of the resins used in manufacturing and reach the lungs as part of the dust particles inhaled during the working processes (cutting, drilling, polishing, etc.). Recently, Halls and colleagues have detected measurable concentrations of a wide range of VOCs emitted when cutting ES [ 42 ]. Although we do not know the pathogenic role of these compounds in ES workers, it should be taken into account that subchronic exposure to low-dose VOCs (formaldehyde, benzene, toluene, and xylene) produces bronchial and lung inflammation in animal models [ 43 ] and some low molecular weight PAHs, such as phenanthrene and fluorene, induce oxidative stress and inflammation in human lung epithelial cells and the combined action of both is more potent than individually [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to provide an exact reason for this, except to suggest that a combination of the composition, processing parameters and particle measurement technique would affect the result obtained. In this connection it is worth mentioning the work of Hall et al (2022) [ 31 ], who characterized and compared dust emissions and respirable crystalline silica (RCS) in natural and artificial stones, using XRD and scanning electron microscopy, where a wide range aerosol spectrometer was used to measure the particle size distribution. They reported that the higher the silica content in the original stone, the higher the level of silica found in the dust emission during processing of the stone.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, rotational, dispersion, MQL (minimum quantity lubricant), and tool path polishing were investigated by these researchers (Saidi et al (2015) [ 27 ], Songmene et al (2018) [ 20 , 21 ] and Saidi et al (2018) [ 28 ]). Despite the health hazards associated with granite polishing, there appear to be only a few studies on silica dust characterization, those of Carrieri et al (2020) [ 29 ], Ramkissoon et al (2022) [ 30 ], and Hall et al (2022) [ 31 ], particularly in light of increasing cases of accelerated silicosis related to the use of engineered (artificial) stones in the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…California's first reported outbreak in 2019 included six cases of silicosis diagnosed in workers under age 60, including two fatalities of workers in their 30s 6 . The elevated risk for accelerated silicosis in these workers has been attributed to the high silica content of engineered stone (generally > 90%), compared with natural stone; exposure to large amounts of respirable dust generated from procedures including cutting and grinding engineered stone, especially in the absence of engineering controls such as wet methods and local exhaust ventilation; and the increased cytotoxicity of freshly fractured crystalline silica particles 12–14 . The variability of engineered stone composition, both in terms of silica crystal forms (e.g., alpha quartz, cristobalite, or tridymite) and nonsilica components (e.g., resins, hardening agents, or pigments), further complicates our understanding of what characteristics of these materials may contribute to their potential to cause accelerated silicosis 15 …”
Section: Introductionmentioning
confidence: 99%
“…6 The elevated risk for accelerated silicosis in these workers has been attributed to the high silica content of engineered stone (generally > 90%), compared with natural stone; exposure to large amounts of respirable dust generated from procedures including cutting and grinding engineered stone, especially in the absence of engineering controls such as wet methods and local exhaust ventilation; and the increased cytotoxicity of freshly fractured crystalline silica particles. [12][13][14] The variability of engineered stone composition, both in terms of silica crystal forms (e.g., alpha quartz, cristobalite, or tridymite) and nonsilica components (e.g., resins, hardening agents, or pigments), further complicates our understanding of what characteristics of these materials may contribute to their potential to cause accelerated silicosis. 15 To decrease worker RCS exposure and the burden of silicosis, the US Occupational Safety and Health Administration (OSHA) updated the RCS standard in 2016, which was also adopted by the California Division of Occupational Safety and Health (Cal/OSHA).…”
mentioning
confidence: 99%